2023
DOI: 10.1109/tai.2021.3137091
|View full text |Cite
|
Sign up to set email alerts
|

Building Trustworthy AI Solutions: A Case for Practical Solutions for Small Businesses

Abstract: Building trustworthy AI solutions, whether in academia or industry, must take into consideration a number of dimensions including legal, social, ethical, public opinion and environmental aspects. A plethora of guidelines, principles and toolkits have been published globally, but have seen limited grassroots implementation, especially among small and medium sized enterprises (SME), mainly due to lack of knowledge, skills, and resources. In this paper, we report on qualitative SME consultations over two events t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…The general lifecycle or development process of a ML-based AI system [75] or product [76] often involves the following stages: business analysis, data engineering, ML modeling, model deployment, and operation and monitoring. Usually, the lifecycle of AI products starts from the business analysis, which mainly involves identifying and understanding the business problem to be solved and business metrics (or criteria of success).…”
Section: Key Ethical Issues Associated With Each Stage Of the Ai Syst...mentioning
confidence: 99%
“…The general lifecycle or development process of a ML-based AI system [75] or product [76] often involves the following stages: business analysis, data engineering, ML modeling, model deployment, and operation and monitoring. Usually, the lifecycle of AI products starts from the business analysis, which mainly involves identifying and understanding the business problem to be solved and business metrics (or criteria of success).…”
Section: Key Ethical Issues Associated With Each Stage Of the Ai Syst...mentioning
confidence: 99%
“…There is abundance of ethical toolkits that could be applied within the context of the GMAIF project to help organizations and businesses develop responsible and trustworthy AI [36]. Crockett et al [37] evaluated and ranked 77 published toolkits based on 33 evaluation criteria which included: toolkit scope in addressing identified SME barriers to adoption; human-centric AI principles, relevance to specific AI lifecycle stages, and key themes around responsible AI and practical usability [37]. The results of this study showed that there is no one-sizefits-all toolkit that addresses all criteria and is suitable for all organizations, including SMEs.…”
Section: B Principles Polices and Framework Of 'Ethical Ai'mentioning
confidence: 99%
“…The results of this study showed that there is no one-sizefits-all toolkit that addresses all criteria and is suitable for all organizations, including SMEs. This research therefore selects some of the most promising toolkits and practices identified by Crockett et al [37] and applies them within the context of the GMAIF project. Additionally, it explores some approaches that this prior work fails to consider and evaluate.…”
Section: B Principles Polices and Framework Of 'Ethical Ai'mentioning
confidence: 99%
See 1 more Smart Citation
“…Morley et al [43] proposes a typology of AI ethics approaches condensed from a variety of toolkits, also critiquing toolkits' lack of usability and their focus on individuals rather than social groups. Crockett et al [12] analyze 77 AI ethics toolkits, finding that many lack instructions or training to facilitate adoption. They focus on the toolkits' dominant principles, product lifecycle stages, and measure how well they may be adopted by small and medium enterprises.…”
Section: Introductionmentioning
confidence: 99%